DNA content of Spermatozoa with respect to Seminal Sperm Concentration using a Microchemical Spectrophotometric Method - Daoud, Munaf S.; AL- chalabi, Faraid A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: To determine the DNA content in subfertile patients and to correlate it with seminal sperm concentration.Design: Prospective observational study.Setting: College of Medicine, Dept. of Physiological chemistry and Institute for embryo Research and infertility treatment-University of Baghdad.The study was conductedthrough years 2004-2005.Methods: A random sample of 61 subfertile male patients undergoing semen evaluation and aged from 20-45 years were studied. Semen samples were assessed for seminal spermconcentration microscopically and were classified into 3 different groups according to count (million/ml).Then sperm D N A content (μg/ml) was estimated using a microchemicalspectrophotometric method.Results: The three groups were statistically of significant difference( P 0.05)correlation was observed in the other two groups (Gr. I & Gr. II ).Conclusion: Significant positive correlation was obtained between sperm concentration and DNA content. in the oligozoospermic subfertile patient , but no significant correlation was found in the normozoopermic patients . D N A content per spermatozoan from oligozoospermic patients was higher than that in normozoospermic patients.